Odontogenic keratocyst: imaging features of a benign lesion with an aggressive behaviour - Andrea Borghesi; Cosimo Nardi; Caterina Giannitto; Andrea Tironi; Roberto Maroldi; Francesco Di Bartolomeo; Lorenzo Preda (Insights into Imaging, 2018)
Abstract The latest (4th) edition of the World Health Organization (WHO) Classification of Head and Neck Tumours, published in January 2017, has reclassified keratocystic odontogenic tumour as odontogenic keratocyst. Therefore, odontogenic keratocysts (OKCs) are now considered benign cysts of odontogenic origin that account for about 10% of all odontogenic cysts. OKCs arise from the dental lamina and are characterised by a cystic space containing desquamated keratin with a uniform lining of parakeratinised squamous epithelium. The reported age distribution of OKCs is considerably wide, with a peak of incidence in the third decade of life and a slight male predominance. OKCs originate in tooth-bearing regions and the mandible is more often affected than the maxilla. In the mandible, the most common location is the posterior sextant, the angle or the ramus. Conversely, the anterior sextant and the third molar region are the most common sites of origin in the maxilla. OKCs are characterised by an aggressive behaviour with a relatively high recurrence rate, particularly when OKCs are associated with syndromes. Multiple OKCs are typically associated with the nevoid basal cell carcinoma syndrome (NBCCS), an autosomal dominant multisystemic disease. Radiological imaging, mainly computed tomography (CT) and, in selected cases, magnetic resonance imaging (MRI), plays an important role in the diagnosis and management of OKCs. Therefore, the main purpose of this pictorial review is to present the imaging appearance of OKCs underlining the specific findings of different imaging modalities and to provide key radiologic features helping the differential diagnoses from other cystic and neoplastic lesions of odontogenic origin. Key Points • Panoramic radiography is helpful in the preliminary assessment of OKCs. • CT is considered the tool of choice in the evaluation of OKCs. • MRI with DWI or DKI can help differentiate OKCs from other odontogenic lesions. • Ameloblastoma, dentigerous and radicular cysts should be considered in the differential diagnosis. • The presence of multiple OKCs is one of the major criteria for the diagnosis of NBCCS.